Reinforcement of aluminum matrix by carbon nano tubes and nano alumina using powder metallurgy method - Ostovan, Farhad (2015)
For the past few years, particulate reinforced aluminum matrix composites (AMCs) have attracted more attention in aerospace, automotive and military industries due to their outstanding mechanical properties including high strength to weight ratio, good wear resistance, good environmental resistance as well as lower costs of production. Besides, AMCs are attractive in engineering applications for weight critical applications which may assist in energy saving along with reduction in the cost. With its low density, aluminum (Al) is a candidate of interest, but further strengthening is needed. The strengthening and development of aluminum has become a critical issue, because only a few materials have been proposed to the industry to strengthen the aluminum matrix. For those proposed materials, fabrication methods and their parameters in order to disperse reinforcements, especially nano reinforcements, within aluminum matrix are still under close scrutiny by researchers all around the world. Because of tangled nature of nano reinforcements, the dispersion of these reinforcements in aluminum matrix is a difficult task and a proper technique to fabricate nano AMCs is needed. In this work, the benefits and limitations of adding Carbon Nano Tubes (CNTs) and Nano Alumina (n-Al2O3) to strengthen the aluminum matrix have been investigated with an emphasis on mechanical milling process and its effects on both nano reinforcement and aluminum matrix. Mechanical milling for different times of 0.5, 2, 5, 8 and 12 h was used to do mechanical alloying of different nano reinforcement contents with aluminum powder. Composite powders were then compacted and sintered at 530 °C. Micro-structural characterization of powders, grain refining analysis through XRD analysis, interfacial bonding assessment through micro structural observation of polished surface of sintered composites, the changes in the density and dimensions of sintered compacts as well as mechanical properties of Al-CNT and Al-Al2O3 composites were measured and compared. Micro structural characterizations showed that, mechanical alloying via ball milling could homogenously disperse CNTs within aluminum matrix. Dispersion uniformity decreased with an increase in the amount of CNTs from 2 wt% up to 5 wt% and 10 wt%. However, further increasing the time of milling caused damage to the CNTs structure and formation of Al4C3 phase. On the other hand, n-Al2O3 dispersed homogenously within aluminum matrix even after adding up high amount of this nano reinforcement to the matrix. Furthermore, mechanical milling offered the advantages of aluminum strengthening through grain refinement and strain hardening. As it was expected for samples fabricated by powder metallurgy processing, nano composite compression and sintering have presented several challenges as it resulted in porous structures, dimension growth and lack of bonding due to the sintering process. Results showed that nano composites which were milled for longer times had higher density after sintering. A minimum densification of 89% was achieved for all specimens. However, attempts to produce dense parts of Al-10CNTs failed due to excessive increase in the dimensions in the presence of CNTs clusters and agglomerations. Micro and nano hardness and Young‘s modulus of Al-CNTs and Al-Al2O3 nano composites as well as compression properties of Al-Al2O3 were measured. Comparison of the results with the previous studies indicated that higher hardness and Young‘s modulus were obtained from the addition of CNTs versus n-Al2O3. On the other hand, in the case of compressive strength of nano composites, an increase in the n-Al2O3 resulted in an increase in compressive stress at break point of 689 MPa, where a homogenous dispersion of nano reinforcement was observed.